An Alternative Approach to Testing Dual Labour Market Theory - Andrey Launov (Institute for the Study of Labor (IZA), 2004)
In this paper we suggest an alternative approach to testing for the dual structure of the labour market. The novelty of the suggested approach is that rather than considering wage determination we concentrate on the turnover. To perform the test we suggest using a latent class count data framework, which allows modelling the turnover in the unobserved primary and secondary markets in the appropriate way. To illustrate the suggested approach we apply our methodology to the German labour market data. Our testing procedure finds no support for the predictions of the dual labour market theory. We also consider the problem of inconclusiveness of the test for involuntary confinement to the secondary market.
Keywords: J42; 330; segmented market; dual labour market; count data; latent class model; Dualer Arbeitsmarkt; Arbeitsmarktsegmentierung; Arbeitsmobilität; Schätzung; Deutschland